Perkembangan Rumah Adat Di Kepulauan Riau - Oki Supriadi (Saraswati)
The cultural wealth of the archipelago as the top of regional culture should be appreciated and preserved. One of the traditional heritage is Malay Traditional House which is located in Kepulauan Riau ( Riau Archipelago ) is worth to be studied its existance after passing through various conditions that afflict the region. The purpose of this research is to know the history of the establishment of the building or The Malay House, especially The Malay Traditional House in Kepulauan Riau. The changes of form that happen and the philosophy of Ornamental Style and Theme ( motifs ) that contain in it, of course have been many changes during by the challenges of the society. Those aspects is investigated, so that can obvious, and be understood for the values which is contained in art tradition for enrich the references that has been exist before, and become the basis in implement it in everyday life. The results of this research show that Kepulauan Riau’s Traditional House has experienced long way, so it is natural if the shapes is change, become a shapes like today. That shape appears because of the acculturation with others culture they are ; Europe, Arabic/Middle East, China, India, Java and Bugis. The entry of a nation or an others tribe to Malay region and then merged into the local tradition by wedding, trading or another way which is at the end, give the influences to the Malay culture itself. As well as the theme ( Motifs ) that contained in the decorations of the traditional house, have a deep meaning that indicates philpsophy values that should be upheld in its society life. The very striking thing is the prohibition or restrictions of the use of certain Ornamental Style. According to the certain of the Malay tradition motifs like Muhammad Bertangkup ( calligraphy ), Naga Berjuang ( Struggling Dragon ), Cogan, is not allowed to used by common society. Those motifs is may only use by sultan, king or the great empire. The acculturation that occured in Malay culture now contributes for the enrich of that Malay culture without losing the values or the shapes of the original culture.